The French eco-neighbourhood evaluation model: Contributions to sustainable city making and to the evolution of urban practices. (1st July 2016) - Chastenet, Cédissia About-de; Belziti, Daniela; Bessis, Bruno; Faucheux, Franck; Le Sceller, Thibaut; Monaco, François-Xavier; Pech, Pierre
Abstract: In this article we discuss whether the French eco-neighbourhood policy tool may be considered as an original experimentation in sustainable urban planning. From scientific literature across a number of countries and especially in European context, we present what kind of policies may achieve eco-neighbourhoods. Then we present what the French framework is, and what tools to promote and elaborate eco-neighbourhoods there are in France. Thirdly, in fact, both French policies, national and local, concerning eco-neighbourhood projects, seem to integrate means of assessing urban projects and this assessment achieves a kind of certification. While the Ministry in charge of Urban Planning has developed the national EcoQuartier ("EcoNeighbourhood" in English) certification, the City of Paris and other local authorities have designed similar tools, which integrate a large number of parameters dealing with urban sustainability and which are designed to evolve over time. Finally, we discuss whether the French tool is really original and whether it prefigures new practices in the field of sustainable urban development. Graphical abstract: Highlights: We explore the question of eco-neighbourhood policy tools. We study scientific literature across a number of countries. We show how social goals are usually given less importance than they deserve. We present French tools to promote and elaborate eco-neighbourhoods. We explain that French tools are integrative, with dynamic indicators.